Aerospace series. Steel X8CrNiTi18-10 (1.4878/1.4544). Annealed. Reference heat treatment: softened. Hollow bars. 5 mm ≤ a ≤ 12 mm. (5th December 2019) - British Standards Institution,
No abstract available